The Arabidopsis Vacuolar Sorting Receptor1 Is Required for Osmotic Stress-Induced Abscisic Acid Biosynthesis - Wang, Zhen-Yu (Plant Physiol, 2015)
Osmotic stress activates the biosynthesis of the phytohormone abscisic acid (ABA) through a pathway that is rate limited by the carotenoid cleavage enzyme 9-cis-epoxycarotenoid dioxygenase (NCED). To understand the signal transduction mechanism underlying the activation of ABA biosynthesis, we performed a forward genetic screen to isolate mutants defective in osmotic stress regulation of the NCED3 gene. Here, we identified the Arabidopsis (Arabidopsis thaliana) Vacuolar Sorting Receptor1 (VSR1) as a unique regulator of ABA biosynthesis. The vsr1 mutant not only shows increased sensitivity to osmotic stress, but also is defective in the feedback regulation of ABA biosynthesis by ABA. Further analysis revealed that vacuolar trafficking mediated by VSR1 is required for osmotic stress-responsive ABA biosynthesis and osmotic stress tolerance. Moreover, under osmotic stress conditions, the membrane potential, calcium flux, and vacuolar pH changes in the vsr1 mutant differ from those in the wild type. Given that manipulation of the intracellular pH is sufficient to modulate the expression of ABA biosynthesis genes, including NCED3, and ABA accumulation, we propose that intracellular pH changes caused by osmotic stress may play a signaling role in regulating ABA biosynthesis and that this regulation is dependent on functional VSR1.